Understanding physiotherapy and physiotherapy services: exploring the perspectives of adults living with cerebral palsy. Issue 8 (10th April 2023) - Cook, Gemma; Cassidy, Elizabeth; Kilbride, Cherry
Abstract: Purpose: To understand physiotherapy and physiotherapy services from the perspectives of adults with cerebral palsy (CP). Methods: Twenty-two adults with CP (15 women, 7 men), from across the UK, aged between 23 and 51 years, Gross Motor Function Classification System I-V, were interviewed about their experiences of physiotherapy and physiotherapy services. Participants were recruited through advertisements placed with relevant national organisations. The interviews were transcribed and analysed according to principles of Reflective Lifeworld Research. A second analysis examined the findings in relation to Donabedian's structure-process-outcome framework for healthcare quality. Results: Specialist services for adults with CP were described as scarce, unknowable, complex and disconnected through the life course. Specific problems included; structural dimensions such as access to and organisation of services, signposting to services and access to expert advice; process dimensions including a lack of attention to patients' perspectives, needs, priorities, experience and expertise; and outcome dimensions for example the negative impact of physiotherapy service configurations on health, well-being and quality of life. Conclusion: Study findings support grassroots calls to radically improve and increase physiotherapy services for adults with CP. Accessible and widely available specialist services, information and advice across the life course would do much to address unmet need. Implications for Rehabilitation: Adults with CP found it difficult to identify and access specialised physiotherapy services and to obtain information and advice to help them best manage their condition. Adults with CP need physiotherapy services throughout the different phases of their lives, to meet their present needs, and to anticipate and, where possible, to prevent future needs. Participants highly valued person-centred physiotherapy and we recommend this approach is adopted as the foundational philosophy guiding physiotherapy services and interventions for adults with CP. More specialist physiotherapy services are urgently needed to meet the needs of adults with CP in the UK.